Future changes to the intensity and frequency of short‐duration extreme rainfall. (27th August 2014) - Westra, S.; Fowler, H. J.; Evans, J. P.; Alexander, L. V.; Berg, P.; Johnson, F.; Kendon, E. J.; Lenderink, G.; Roberts, N. M.
Abstract Evidence that extreme rainfall intensity is increasing at the global scale has strengthened considerably in recent years. Research now indicates that the greatest increases are likely to occur in short‐duration storms lasting less than a day, potentially leading to an increase in the magnitude and frequency of flash floods. This review examines the evidence for subdaily extreme rainfall intensification due to anthropogenic climate change and describes our current physical understanding of the association between subdaily extreme rainfall intensity and atmospheric temperature. We also examine the nature, quality, and quantity of information needed to allow society to adapt successfully to predicted future changes, and discuss the roles of observational and modeling studies in helping us to better understand the physical processes that can influence subdaily extreme rainfall characteristics. We conclude by describing the types of research required to produce a more thorough understanding of the relationships between local‐scale thermodynamic effects, large‐scale atmospheric circulation, and subdaily extreme rainfall intensity.